Resistance Level and Enzyme Activity of Spodoptera litura F. to Chlorpyrifos and Their Sensitivity to the Oil Formulation of Azadirachta indica Juss. and Cymbopogon nardus (L.) Rendl. - R. Arif Malik Ramadhan; Neneng Sri Widayani; Danar Dono; Yusup Hidayat; Safri Ishmayana (AGRIVITA, Journal of Agricultural Science, 2022)
This study aimed to obtain resistance information of S. litura from Karangpawitan and Lembang districts (West Java, Indonesia) against chlorpyrifos insecticides (200 g/l) and their sensitivity to oil mixture of A. indica and C. nardus (1:1) using feeding and topical assay. The activity of acetylcholinesterase, esterase, and glutathione s-transferase from S. litura larvae in both populations were tested to determine their role in insect resistance. Results showed that S. litura population from Lembang had a higher level of resistance to chlorpyrifos compared to Karangpawitan. The sensitivity of the two S. litura populations had a relatively similar resistance ratio (RR) value of less than 1 to botanical insecticide. These indicated that resistant population could be controlled by a mixture of this botanicals insecticide. Enzyme activity test indicated that chlorpyrifos at a concentration of 0.26% could inhibit the acetylcholinesterase activity of insect population from Karangpawitan by 98.66% while those from Lembang, it was only 35.31%. Specific activity of esterase from Karangpawitan was 13.37 units/mg while Lembang population was 119.65 units/mg. The specific activity of the Glutathione S-Transferase (GST) of Karangpawitan population was 1140.82 units/mg while Lembang population was 793.73 units/mg. The high activity of the three enzymes could be responsible for resistance of S. litura larvae to chlorpyrifos.